„Silę ucho”, czyli co słychać w przekładzie. Niemieckojęzyczne warianty wiersza Skakanka ufoistki Mirona Białoszewskiego na tle zabiegów „przekładania” codzienności na język poetycki - Aleksandra Burba (Poznańskie Studia Polonistyczne. Seria Literacka, 2014)
The article has been derived from a chapter of an MA thesis on everyday speech in Miron Białoszewski’s work. The text focuses on exposition of methodological assumptions - the notion of everyday speech and its translation into poetic language in Białoszewski’s works. In particular, the article discusses a series of non-professional translations of the poem UFO agent’s skipping rope into German, as an example of the functioning of the dominant of everyday speech in translations of Białoszewski’s poetry.